Mainstreaming Marxism: on the anarchic structure of world economy. - Morton, Adam David (International Affairs, 2023)
This article carves out a focus on certain authorized mainstream perspectives and their theorizations of world order, and how they have become dominant at the expense of excluded and silenced contributions. This task begins, first, by asserting that the anarchic conditions of world order have been mainstreamed at the expense of contributions to Marxist political economy. Here, my focus extends the methodological approach of juxtaposition to explore competing understandings of anarchic orders in Kenneth Waltz's and Nikolai Bukharin's work to disclose, in the latter, the anarchic structure of world capitalism. Second, the method of juxtaposition enables me to cast attention to the parallel profiles of E. H. Carr and C. L. R. James and their weighty understandings of world revolution to reveal, in the latter, neglected classed conditions of racial capitalism. In a fresh manner, then, my approach juxtaposes key figures that have been present (Waltz, Carr) and absent (Bukharin, James) in understanding world order through the anarchic structure of the world economy and racial capitalism. In conclusion, the argument left for academic study and the elucidation of policy is the extent to which a necessarily historical materialist moment to understanding world order can and should be further extended and deepened.